Volumetric Properties for the Aqueous Solution of Yttrium Trichloride at Temperatures from 283.15 to 363.15 K and Ambient Pressure. (9th November 2021) - Jiang, Zhenzhen; Ma, Chi; Liu, Gaoling; Sun, Kangrui; Li, Mingli; Guo, Yafei; Meng, Lingzong; Deng, Tianlong
Abstract : To effectively develop the rare earth elements resources from the geothermal waters, it is essential to understand the volumetric properties of the aqueous solution system to establish the relative thermodynamic model. In this study, densities of YCl3 (aq) at the molalities of 0.08837–1.60639 mol·kg −1 from 283.15 K to 363.15 K at 5 K intervals and ambient pressure were measured experimentally by an Anton Paar digital vibrating-tube densimeter. Based on experimental data, the volumetric properties including apparent molar volume ( V ϕ ) and the coefficient of thermal expansion of the solution ( α ) of the binary systems (YCl3  + H2 O) were derived. The 3D diagram ( m i, T, V ϕ ) of apparent molar volumes against temperature and molality was plotted. On the basis of the Pitzer ion-interaction model of electrolyte, the Pitzer single-salt parameters (β MX 0 v, β MX 1 v, and C MX v ) for YCl3 and temperature-dependence equation F ( i, p, T ) =  a 1  +  a 2 ln(T/298.15) +  a 3 (T-298.15) +  a 4 /(620-T) +  a 5 (T-227) as well as their coefficients a i ( i  = 1–5) in the binary system were obtained for the first time. The values of Pitzer single-salt parameters of YCl3 agree well with the calculated values corresponding to the temperature-dependence equations, indicating that single-salt parameters and temperature-dependent formula obtained in this work are reliable.